Electric insulation fireproof plugging potting adhesive
By using silicone base material, fire-resistant additives, high-temperature fillers and glass fiber mesh in power insulated fire-proof sealing glue, combined with magnetic detonation technology, the problems of degradation of existing materials and insufficient fire resistance in humid environments are solved. The combination of rapid curing and high strength is achieved, ensuring the material's high temperature and weather resistance, and providing long-lasting protection for the power system.
Patent Information
- Application Number
- CN202411509923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
AI Technical Summary
The existing power insulated fire-proof sealing glue filling materials have deteriorated performance in humid environments, long curing time, insufficient fire resistance and high temperature resistance, and are prone to aging and cracking problems, affecting their fire resistance and insulation effects.
Power-insulated fire-proof sealing glue including silicone base material, fire-retardant additives, high-temperature resistant fillers, environmentally friendly flame retardants and fragmented glass fiber mesh can be used to achieve rapid curing and high-strength combination through modified materials and magnetic detonation technology to ensure The material is high temperature resistance, moisture resistance and long-term stability.
It realizes rapid curing of power insulation fireproof sealing glue, excellent high-temperature resistance, low-temperature resistance and chemical corrosion resistance, ensures the flexibility and weather resistance of the material, and provides long-lasting power through non-toxic and harmless flame retardant effects. System protection.
Smart Images

Figure CN119242261A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electric power engineering, and specifically to electric power insulation fireproof material technology. Background Art
[0002] Power insulation fireproof plugging glue filling technology is widely used in power systems, especially in key locations such as cable penetration holes, junction boxes, cable trays, etc., to prevent the spread of fire and provide electrical insulation protection. This technology ensures the safe operation of the power system by filling and plugging these potential fire source propagation paths.
[0003] In the prior art, the fireproof sealing glue for power insulation mainly includes sealants prepared by inorganic materials (such as gypsum and cement) and sealants prepared by organic materials (such as polyurethane and epoxy resin).
[0004] Sealants made from inorganic materials have good fire resistance, but they take a long time to cure and their performance deteriorates in humid environments; while sealants made from organic materials have a fast curing speed, but their fire resistance and high temperature resistance are relatively insufficient.
[0005] In addition, these materials are prone to aging, cracking and other problems during long-term use, affecting their fire prevention and insulation effects.
[0006] Therefore, the development of a new type of power insulation fireproof sealing glue material with fast and controllable curing, excellent high temperature resistance, moisture resistance and long-term stability has become a key requirement for current technological development. Summary of the invention
[0007] The purpose of the present invention is to provide a fireproof plugging glue for electric insulation to solve at least one of the above technical problems.
[0008] The technical problem solved by the present invention can be achieved by adopting the following technical solutions:
[0009] Power insulation fireproof plugging glue, including silicone base material, fireproof additives, high temperature resistant filler, and environmentally friendly flame retardant, and doped with fragmented glass fiber mesh, using the fragmented glass fiber mesh as filler;
[0010] The organic silicon base material includes 107 silicone oil, a cross-linking agent, a silane coupling agent and a catalyst;
[0011] Wherein, in terms of weight percentage, the organic silicon base material includes 70.8-87.2% of 107 silicone oil, 0.03-0.07% of a cross-linking agent, 0.001-0.01% of a silane coupling agent, and 0.00007-0.005% of a catalyst;
[0012] Fire retardant additive 0.007~0.006%;
[0013] High temperature resistant filler 0.002~0.007%;
[0014] Environmentally friendly flame retardant 0.07~0.26%;
[0015] The glass fiber mesh comprises a mesh body and expanded glass fibers;
[0016] The net body is woven with warp and weft;
[0017] Both the warp and weft threads are made of fiberglass;
[0018] The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers;
[0019] The diameter of glass fiber is 5 to 8 μm;
[0020] The area of the mesh is 0.5~1.8mm 2 , mesh area is 0.01~0.15mm 2 ;
[0021] The length of the expanded glass fiber is 0.8 to 2 mm;
[0022] Measured by volume, there are 2 to 4 glass fiber meshes per cubic centimeter.
[0023] In the above design, the power insulation fireproof plugging glue uses polyurethane modified silicone material, which has been significantly improved in performance and has excellent high temperature resistance, low temperature resistance and chemical corrosion resistance. At the same time, modified dimethyl vinyl siloxane is also used, which performs well in improving the flexibility and weather resistance of the material. In addition, in order to ensure the environmental performance of the product, inorganic environmentally friendly flame retardant materials are specially added. This material not only has a good flame retardant effect, but also does not produce toxic and harmful smoke and gas. After the above-mentioned modified design, this design can be cured within 10 to 15 after being exposed to the air, and the high temperature resistance of the cured product reaches 550 to 600 ° C. Its beneficial effects are as described above.
[0024] In the above design, the 5-8μm glass fiber woven mesh has good softness and certain toughness. The area of the mesh is 0.5-1.8 square millimeters. The fragmented glass fiber mesh formed is not easy to be tangled after being mixed into the power insulation fireproof sealing glue as a filler. The mesh area is 0.01-0.15 square millimeters, allowing the silicone base material to pass through the mesh and the strength of the combination with the fiber mesh is stronger.
[0025] In the above design, the length of the expanded glass fiber is 0.8 to 2 mm. In terms of volume, there are 2 to 4 glass fiber meshes per cubic centimeter. The beneficial effect is that while ensuring that the number of glass fiber meshes per unit volume is moderate, the expanded glass fibers are staggered as much as possible to form a three-dimensional network structure, thereby improving the overall strength.
[0026] Further, the 107 silicone oil has a viscosity of one of 5000CP, 10000CP, 20000CP, and 40000CP;
[0027] The crosslinking agent is one or more of methyltrimethoxysilane, vinyltrimethoxysilane and tetramethoxysilane;
[0028] The silane coupling agent is one or more of KH330, KH550 and KH570;
[0029] The catalyst is one of dibutyltin dilaurate, stannous octoate and dibutyltin diacetate.
[0030] Furthermore, the fire retardant is one of o-aminophenylarsenic acid with polyether polyol as carrier and zinc methyl arsenate with polyether polyol as carrier;
[0031] The environmentally friendly flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, zinc borate and melamine phosphate.
[0032] Furthermore, the high temperature resistant filler is one or more of white carbon black, silicon dioxide, and calcium carbonate;
[0033] White carbon black is white carbon black prepared by gas phase method or precipitation method, with an average particle size of 5 to 35 μm;
[0034] The particle size of calcium carbonate is 4000 mesh and the moisture content is <0.1%.
[0035] Furthermore, when drawing the glass fiber as one of the warp and weft, the glass fiber passes through a space where the ferroferric oxide powder dust floats in the air in a molten state, and is bonded with the ferroferric oxide powder;
[0036] When drawing, the glass fiber, which is another kind of warp and weft, passes through the space where graphite dust floats in the air in a molten state and is bonded with graphite powder;
[0037] The particle size of the ferroferric oxide powder is 50 to 150 nm;
[0038] The particle size of graphite powder is 6 to 10 μm.
[0039] In the above design, ferroferric oxide powder and graphite powder are bonded in the molten state of glass fiber. The beneficial effect is that the bonding is strong and uniform, the adhesive can be omitted, the bonding structure will not be damaged under high and low temperatures, the long-lasting bonding strength between the glass fiber and the silicone base material is guaranteed, and the glass fiber can withstand high-temperature electromagnetic induction heating.
[0040] As one of the warp or weft threads, the glass fiber is bonded with ferroferric oxide powder, which has soft magnetic properties.
[0041] It is also equipped with a device consisting of an electromagnet connected to a signal generator, which can emit a low-frequency magnetic field. The glass fiber bonded with ferroferric oxide powder drives the entire glass fiber mesh to vibrate under the action of the low-frequency magnetic field. The beneficial effects are: first, the vibration of the glass fiber mesh can play a stirring role, so that the components of the power insulation fireproof sealing glue are better mixed; second, the vibration of the glass fiber mesh can eliminate bubbles in the colloid and improve the quality of curing; third, the vibration of the glass fiber mesh can make the contact between the fiber mesh and the power insulation fireproof sealing glue more firm and eliminate surface tension.
[0042] As the other one of the warp or weft, the glass fiber is bonded with graphite powder, and the graphite powder in the fluid glue makes the fluid glue have a certain conductivity.
[0043] It is also equipped with an electromagnetic induction heating device, which is set near the fluid glue. The electromagnetic induction heating device can emit a high-frequency magnetic field. The glass fiber is bonded with ferroferric oxide powder, which has soft magnetic properties and can introduce the magnetic field deep into the fluid glue to form a relatively uniform magnetic field distributed in the fluid glue, thereby making the conductive fluid glue relatively uniformly heated, thereby increasing the ambient temperature during curing. Its beneficial effect is that the heating temperature of the fluid glue can be controlled by changing the frequency and amplitude of the magnetic field through the electromagnetic induction heating device, thereby controlling the efficiency and speed of curing.
[0044] Furthermore, it also includes gas storage particles doped with gas storage particles detonated by magnetic force, using the gas storage particles as filler;
[0045] The gas storage particles have an airtight membrane filled with air at 1.15 to 1.3 atmospheres and a humidity of 70 to 90%.
[0046] Also included is a magnetic needle, which includes a needle tip and a needle body, the needle tip is made of a soft magnetic material, and the needle body is made of a non-magnetic material;
[0047] The volume of gas storage particles is 2-3 mm 3 ;
[0048] There are 2 to 4 gas storage particles per cubic centimeter.
[0049] For further optimization, the membrane of the gas storage particles is made of polyvinyl chloride; the needle tip is made of low-carbon steel; and the needle body is made of ABS plastic.
[0050] In the above design, in order to further improve the curing speed, gas storage particles are added to the power insulation fireproof sealing glue. The gas storage particles are filled with humid air with an air humidity of 70-90%. Magnetic needles for detonating the gas storage particles are also provided in the gas storage particles.
[0051] The invention is also equipped with a device, including an oscillating circuit connected to an electromagnet to generate a magnetic field with periodic direction changes. The electromagnet is close to the colloid, and under the action of the magnetic field, the needle tip of the magnetic needle is guided to pierce the film made of polyvinyl chloride of the gas storage particles. The polyvinyl chloride has a certain elasticity and will burst after being pierced by the needle tip, thereby releasing the humid air in the gas storage particles inside the power insulation fireproof sealing glue. The beneficial effect is that the water molecules contained in the released air react chemically with the crosslinking agent inside the power insulation fireproof sealing glue to form a three-dimensional crosslinking network, thereby accelerating the curing efficiency and speed of the power insulation fireproof sealing glue.
[0052] In the above design, the needle tip is made of low-carbon steel and the needle body is made of ABS plastic, which has the beneficial effect of reducing manufacturing costs.
[0053] Furthermore, the preparation method of the power insulation fireproof plugging glue has the following specific preparation steps:
[0054] S1. Activation treatment: Activate the high temperature resistant filler to improve its activity in subsequent reactions;
[0055] S2. Base material mixing: Add the silicone base material and the fire retardant additive into the reactor according to the component ratio, close the reactor, start the vacuum device to draw vacuum in the reactor until the pressure in the reactor is lower than 130 Bar, and start the stirring device to stir to ensure uniform mixing;
[0056] S3. Adding flame retardant: Add environmentally friendly flame retardant materials into the reactor, close the reactor and start the vacuum device to draw vacuum into the reactor until the pressure inside the reactor is lower than 130 Bar, start the stirring device and continue stirring until it is completely uniform;
[0057] S4, dispersion treatment: add the activated high temperature resistant filler into the reactor, close the reactor again, and draw vacuum in the reactor again until the pressure in the reactor is lower than 130 Bar, and then perform dispersion treatment. The dispersion treatment time is 4 to 6 hours to ensure that the high temperature resistant filler is evenly dispersed in the silicone base material;
[0058] S5. Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
[0059] Further optimization, the activation treatment in step S1 is carried out by using ultrasonic dispersion treatment, and the activation treatment lasts for 10 to 30 minutes;
[0060] The stirring time of step S2 is 15 to 45 minutes;
[0061] The stirring time of step S3 is 5 to 15 minutes;
[0062] The dispersion treatment time of step S4 is 4 to 6 hours.
[0063] In the above design, the production cost of preparing power insulation fireproof sealing glue is reduced by stirring the mixture and dispersing under vacuum conditions in the reactor, thereby achieving the purpose of mass production.
[0064] The beneficial effect of the present invention is that, by performing potting treatment inside the power distribution cabinet, comprehensive protection of the power system is achieved. The plugging agent has excellent moisture-proof, waterproof, insulating and anti-condensation properties, and can effectively prevent water and moisture from corroding power equipment.
[0065] The beneficial effect is that the polymer moisture-proof plugging agent not only has the functions of waterproofing and anti-condensation, but also has good insulation performance, which can prevent current leakage and short-circuit accidents. In addition, the plugging agent also has the effect of preventing small animals from entering, avoiding power failures caused by small animals. Its easy-to-expand design makes subsequent maintenance and upgrades more convenient.
[0066] Its beneficial effect also lies in that the plugging agent has a long effective protection time and can provide long-lasting protection for the power system. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0068] Figure 1 is a schematic diagram of a fiberglass mesh in fragmented form;
[0069] Figure 2 It is a schematic diagram of the structure of the network body;
[0070] Figure 3 It is a schematic diagram of the gas storage particle structure.
[0071] Explanation of symbols:
[0072] 1. mesh; 2. expanded glass fiber; 3. gas storage particles; 11. warp; 12. weft; 30. film; 31. magnetic needle. DETAILED DESCRIPTION
[0073] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0074] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0075] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.
[0076] Furthermore, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0077] Power insulation fireproof plugging glue, including silicone base material, fireproof additives, high temperature resistant filler, and environmentally friendly flame retardant, and doped with fragmented glass fiber mesh, using the fragmented glass fiber mesh as filler;
[0078] The organic silicon base material includes 107 silicone oil, a cross-linking agent, a silane coupling agent and a catalyst;
[0079] Wherein, in terms of weight percentage, the organic silicon base material includes 70.8-87.2% of 107 silicone oil, 0.03-0.07% of a cross-linking agent, 0.001-0.01% of a silane coupling agent, and 0.00007-0.005% of a catalyst;
[0080] Fire retardant additive 0.007~0.006%;
[0081] High temperature resistant filler 0.002~0.007%;
[0082] Environmentally friendly flame retardant 0.07~0.26%;
[0083] The glass fiber mesh includes a mesh body 1 and expanded glass fibers 2;
[0084] The net body 1 is woven by warp threads 11 and weft threads 12;
[0085] The warp threads 11 and the weft threads 12 are both made of glass fibers;
[0086] The lengths of at least part of the warp threads 11 and at least part of the weft threads 12 exceed the mesh body 1 to form extended glass fibers 2;
[0087] The diameter of glass fiber is 5 to 8 μm;
[0088] The area of the mesh 1 is 0.5~1.8mm 2 , mesh area is 0.01~0.15mm 2 ;
[0089] The length of the extended glass fiber 2 is 0.8 to 2 mm;
[0090] Measured by volume, there are 2 to 4 glass fiber meshes per cubic centimeter.
[0091] In this embodiment, the power insulation fireproof plugging glue uses polyurethane modified silicone material, which has been significantly improved in performance and has excellent high temperature resistance, low temperature resistance and chemical corrosion resistance. At the same time, modified dimethyl vinyl siloxane is also used, which performs well in improving the flexibility and weather resistance of the material. In addition, in order to ensure the environmental performance of the product, inorganic environmentally friendly flame retardant materials are specially added. This material not only has a good flame retardant effect, but also does not produce toxic and harmful smoke and gas. After the above-mentioned modified design, this design can be cured within 10 to 15 after being exposed to the air, and the high temperature resistance of the cured product reaches 550 to 600 ° C. Its beneficial effects are as described above.
[0092] In this embodiment, the mesh woven from 5-8 μm glass fibers has good softness and certain toughness. The area of the mesh body 1 is 0.5-1.8 square millimeters, and the fragmented glass fiber mesh formed is not easy to be tangled after being mixed into the power insulation fireproof plugging glue as a filler. The mesh area is 0.01-0.15 square millimeters, allowing the silicone base material to pass through the mesh and the strength of the combination with the fiber mesh is stronger.
[0093] In this embodiment, the length of the extended glass fiber 2 is 0.8 to 2 mm. In terms of volume, there are 2 to 4 glass fiber meshes per cubic centimeter. The beneficial effect is that while ensuring that the number of glass fiber meshes per unit volume is moderate, the extended glass fibers 2 are staggered as much as possible to form a three-dimensional network structure, thereby improving the overall strength.
[0094] Further, the 107 silicone oil has a viscosity of one of 5000CP, 10000CP, 20000CP, and 40000CP;
[0095] The crosslinking agent is one or more of methyltrimethoxysilane, vinyltrimethoxysilane and tetramethoxysilane;
[0096] The silane coupling agent is one or more of KH330, KH550 and KH570;
[0097] The catalyst is one of dibutyltin dilaurate, stannous octoate and dibutyltin diacetate.
[0098] Furthermore, the fire retardant is one of o-aminophenylarsenic acid with polyether polyol as carrier and zinc methyl arsenate with polyether polyol as carrier;
[0099] The environmentally friendly flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, zinc borate and melamine phosphate.
[0100] Furthermore, the high temperature resistant filler is one or more of white carbon black, silicon dioxide, and calcium carbonate;
[0101] White carbon black is white carbon black prepared by gas phase method or precipitation method, with an average particle size of 5 to 35 μm;
[0102] The particle size of calcium carbonate is 4000 mesh and the moisture content is <0.1%.
[0103] Furthermore, when drawing, the glass fiber as one of the warp 11 and the weft 12 is in a molten state and passes through a space where ferroferric oxide powder dust floats in the air, and is bonded with ferroferric oxide powder;
[0104] When drawing, the glass fiber, which is another one of the warp 11 and the weft 12, passes through a space where graphite dust floats in the air in a molten state, and is bonded with graphite powder;
[0105] The particle size of the ferroferric oxide powder is 50 to 150 nm;
[0106] The particle size of graphite powder is 6 to 10 μm.
[0107] In this embodiment, ferroferric oxide powder and graphite powder are bonded in the molten state of glass fiber. The beneficial effect is that the bonding is strong and uniform, the adhesive can be omitted, the bonding structure will not be damaged under high and low temperatures, the long-lasting bonding strength between the glass fiber and the silicone base material is ensured, and the glass fiber can withstand high-temperature electromagnetic induction heating.
[0108] As one of the warp threads 11 or the weft threads 12, the glass fiber thereof is bonded with ferroferric oxide powder, and the ferroferric oxide powder has soft magnetic properties.
[0109] It is also equipped with a device consisting of an electromagnet connected to a signal generator, which can emit a low-frequency magnetic field. The glass fiber bonded with ferroferric oxide powder drives the entire glass fiber mesh to vibrate under the action of the low-frequency magnetic field. The beneficial effects are: first, the vibration of the glass fiber mesh can play a stirring role, so that the components of the power insulation fireproof sealing glue are better mixed; second, the vibration of the glass fiber mesh can eliminate bubbles in the colloid and improve the quality of curing; third, the vibration of the glass fiber mesh can make the contact between the fiber mesh and the power insulation fireproof sealing glue more firm and eliminate surface tension.
[0110] As the other one of the warp threads 11 or the weft threads 12, the glass fiber thereof is bonded with graphite powder, and the graphite powder in the fluid glue makes the fluid glue have a certain conductivity.
[0111] It is also equipped with an electromagnetic induction heating device, which is set near the fluid glue. The electromagnetic induction heating device can emit a high-frequency magnetic field. The glass fiber is bonded with ferroferric oxide powder, which has soft magnetic properties and can introduce the magnetic field deep into the fluid glue to form a relatively uniform magnetic field distributed in the fluid glue, thereby making the conductive fluid glue relatively uniformly heated, thereby increasing the ambient temperature during curing. Its beneficial effect is that the heating temperature of the fluid glue can be controlled by changing the frequency and amplitude of the magnetic field through the electromagnetic induction heating device, thereby controlling the efficiency and speed of curing.
[0112] Furthermore, it also includes gas storage particles 3 doped with gas storage particles 3 detonated by magnetic force, with the gas storage particles 3 as filler;
[0113] The gas storage particle 3 has an airtight membrane 30, and the membrane 30 is filled with air at 1.15 to 1.3 atmospheres, and the air humidity is 70 to 90%;
[0114] The device further comprises a magnetic needle 31, which comprises a needle tip and a needle body, wherein the needle tip is made of a soft magnetic material and the needle body is made of a non-magnetic material;
[0115] The volume of gas storage particles 3 is 2-3 mm 3 ;
[0116] There are 2 to 4 gas storage particles per cubic centimeter3.
[0117] For further optimization, the membrane 30 of the gas storage particle 3 is made of polyvinyl chloride; the needle tip is made of low-carbon steel; and the needle body is made of ABS plastic.
[0118] In this embodiment, in order to further improve the curing speed, gas storage particles 3 are added to the power insulation fireproof sealing glue, the gas storage particles 3 are filled with humid air with an air humidity of 70-90%, and magnetic needles 31 for detonating the gas storage particles 3 are also arranged in the gas storage particles 3.
[0119] A device is also provided, including an oscillating circuit connected to an electromagnet to generate a magnetic field with periodic direction changes. The electromagnet is close to the colloid, and under the action of the magnetic field, the needle tip of the magnetic needle 31 is guided to pierce the film 30 made of polyvinyl chloride of the gas storage particles 3. The polyvinyl chloride has a certain elasticity and will burst after being pierced by the needle tip, thereby releasing the humid air in the gas storage particles 3 inside the power insulation fireproof sealing glue. The beneficial effect is that the water molecules contained in the released air react chemically with the crosslinking agent inside the power insulation fireproof sealing glue to form a three-dimensional crosslinking network, thereby accelerating the curing efficiency and speed of the power insulation fireproof sealing glue.
[0120] In this embodiment, the needle tip is made of low-carbon steel and the needle body is made of ABS plastic, which has the beneficial effect of reducing the manufacturing cost.
[0121] Embodiment 1:
[0122] The following steps are involved:
[0123] (1) Activation treatment: (by weight, weigh 5 to 50 parts) a certain amount of fumed silica and silicon dioxide is activated to improve their activity in subsequent reactions;
[0124] (2) Base material mixing: weigh the following raw materials by weight in a reaction kettle: 100 parts of 107 silicone oil (viscosity 5000CP), 5-7 parts of a cross-linking agent (such as methyltrimethoxysilane), 0.3-1 parts of a silane coupling agent (such as KH330), 0.01-0.5 parts of a catalyst (such as dibutyltin dilaurate), 0.8 parts of a glass fiber mesh, and 0.2 parts of a fire retardant additive (such as o-aminophenylarsenic acid with a polyether polyol as a carrier). Close the reaction kettle, start the vacuum machine to evacuate to 130 Bar, and start the stirring device to ensure uniform mixing;
[0125] (3) Flame retardant addition: Add a certain amount of inorganic environmentally friendly flame retardant material (such as magnesium hydroxide), close the reactor, start the vacuum machine to evacuate to 130 Bar, and continue stirring until completely uniform;
[0126] (4) Dispersion treatment: Add the activated filler into the reactor, close the reactor, start the vacuum machine to evacuate to 130 Bar, and perform dispersion treatment for 4 hours to ensure that the filler is evenly dispersed in the base material;
[0127] (5) Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
[0128] Embodiment 2:
[0129] The following steps are involved:
[0130] (1) Activation treatment: (by weight, weigh 5 to 50 parts) a certain amount of fumed silica is activated to improve its activity in subsequent reactions;
[0131] (2) Mixing of base materials: weigh the following raw materials by weight in a reaction kettle: 100 parts of 107 silicone oil with a viscosity of 5000 CP, 6 parts of methyltrimethoxysilane as a crosslinking agent, 0.5 parts of KH550 as a silane coupling agent, 0.1 parts of dibutyltin dilaurate as a catalyst, 0.7 parts of glass fiber mesh, and 0.3 parts of o-aminophenylarsonic acid with polyether polyol as a carrier as a fire retardant additive. Close the reaction kettle, start the vacuum machine to evacuate to 130 Bar, and start the stirring device to ensure uniform mixing;
[0132] (3) Flame retardant addition: Add 20 parts of magnesium hydroxide as an environmentally friendly flame retardant material, close the reactor, start the vacuum machine to evacuate to 130 Bar, and continue stirring until completely uniform;
[0133] (4) Dispersion treatment: Add the activated filler into the reactor, close the reactor, start the vacuum machine to evacuate to 130 Bar, and perform dispersion treatment for 4 hours to ensure that the filler is evenly dispersed in the base material;
[0134] (5) Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
[0135] Embodiment 3:
[0136] The following steps are involved:
[0137] (1) Activation treatment: Activation treatment of silicon dioxide
[0138] (2) Base material mixing: weigh the following raw materials in a reactor by weight: 100 parts of 107 silicone oil with a viscosity of 20,000 CP, 5 parts of vinyl trimethoxy silane as a crosslinking agent, 0.8 parts of KH570 as a silane coupling agent, 0.3 parts of stannous octoate as a catalyst, 0.6 parts of glass fiber mesh, and 0.2 parts of zinc methyl arsenate with polyether polyol as a carrier as a fire retardant additive. Close the reactor, start the vacuum machine to evacuate to 130 Bar, and start the stirring device to ensure uniform mixing;
[0139] (3) Flame retardant addition: Add 15 parts of aluminum hydroxide as an environmentally friendly flame retardant material, close the reactor, start the vacuum machine to evacuate to 130 Bar, and continue stirring;
[0140] (4) Dispersion treatment: Add the activated filler into the reactor, close the reactor, start the vacuum machine to evacuate to 130 Bar, and perform dispersion treatment for 4 hours to ensure that the filler is evenly dispersed in the base material;
[0141] (5) Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
[0142] Embodiment 4:
[0143] The following steps are involved:
[0144] (1) Mixing of base materials: weigh the following raw materials in a reactor by weight: 100 parts of 107 silicone oil with a viscosity of 40,000 CP as a base, 7 parts of tetramethoxysilane as a crosslinking agent, 0.3 parts of a mixed silane coupling agent of KH330 and 0.5 parts of KH550, 0.05 parts of dibutyltin dilaurate as a catalyst, 0.4 parts of o-aminophenylarsonic acid with polyether polyol as a carrier as a fire retardant additive, and 0.6 parts of glass fiber mesh, seal the reactor, start the vacuum machine to evacuate to 130 Bar, start the stirring device, and mix well.
[0145] (2) Flame retardant and filler treatment: Add a mixture of pre-activated and mixed calcium carbonate (particle size of 4000 mesh, moisture content <0.1%) and inorganic environmentally friendly flame retardant material (such as zinc borate), close the reactor, start the vacuum machine to evacuate to 130 Bar, and start the stirring device to stir evenly.
[0146] (3) Dispersion treatment: Dispersion treatment is carried out in a reactor under vacuum for 6 hours;
[0147] (4) Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
[0148] Embodiment 5:
[0149] The following steps are involved:
[0150] (1) Base material preparation: by weight, select: 100 parts of 107 silicone oil with a viscosity of 10000CP, and 5.5 parts of a mixture of methyltrimethoxysilane and tetramethoxysilane (ratio 1:1) as a crosslinking agent;
[0151] (2) Mixing and activation: Add 0.3 parts of KH570 silane coupling agent, 0.2 parts of dibutyltin diacetate catalyst and 0.1 parts of methyl arsenate fire retardant additive with polyether polyol as carrier. At the same time, activate silicon dioxide (synthesized by gas phase method, water content <0.6%);
[0152] (3) Comprehensive mixing: Mix the activated silica with the pre-prepared base material, add 10 parts of environmentally friendly flame retardant (such as melamine phosphate) and 0.5 parts of glass fiber mesh, close the reactor, start the vacuum machine to evacuate to 130 Bar, and start the stirring device to stir evenly for about 5 hours;
[0153] (4) Inspection and packaging: The finished products are subjected to various performance tests and packaged and stored after passing the tests.
[0154] The above embodiments show different material combinations and proportions, aiming to demonstrate the flexibility and wide application potential of the present invention. Each embodiment is carefully designed to ensure that the power insulation fireproof sealing glue has excellent performance.
[0155] Furthermore, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment may not be described, i.e., those features that are not relevant to the best mode presently contemplated for carrying out the invention or those features that are not relevant to implementing the invention.
[0156] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, the development effort will be a routine task of design, fabrication, and production without undue experimentation.
[0157] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. Power insulation fireproof plugging glue, characterized by: It includes an organic silicon base material, a fireproof additive, a high temperature resistant filler, and an environmentally friendly flame retardant, and is doped with a fragmented glass fiber mesh, using the fragmented glass fiber mesh as a filler; The organic silicon base material includes 107 silicone oil, a cross-linking agent, a silane coupling agent and a catalyst; Wherein, in terms of weight percentage, the organic silicon base material includes 70.8-87.2% of 107 silicone oil, 0.03-0.07% of a cross-linking agent, 0.001-0.01% of a silane coupling agent, and 0.00007-0.005% of a catalyst; Fire retardant additive 0.007~0.006%; High temperature resistant filler 0.002~0.007%; Environmentally friendly flame retardant 0.07~0.26%; The glass fiber mesh comprises a mesh body and expanded glass fibers; The net body is woven with warp and weft; Both the warp and weft threads are made of fiberglass; The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers; The diameter of glass fiber is 5 to 8 μm; The area of the mesh is 0.5~1.8mm 2 , mesh area is 0.01~0.15mm 2 ; The length of the expanded glass fiber is 0.8 to 2 mm; Measured by volume, there are 2 to 4 glass fiber meshes per cubic centimeter.
2. The electric power insulation fireproof plugging glue according to claim 1 is characterized by: 107 silicone oil has a viscosity of 5000CP, 10000CP, 20000CP, and 40000CP; The crosslinking agent is one or more of methyltrimethoxysilane, vinyltrimethoxysilane, and tetramethoxysilane; The silane coupling agent is one or more of KH330, KH550 and KH570; The catalyst is one of dibutyltin dilaurate, stannous octoate and dibutyltin diacetate.
3. The electric power insulation fireproof plugging glue according to claim 1 is characterized by: The fire retardant is one of o-aminophenylarsenic acid with polyether polyol as carrier and zinc methyl arsenate with polyether polyol as carrier; The environmentally friendly flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, zinc borate and melamine phosphate.
4. The electric power insulation fireproof plugging glue according to claim 1 is characterized by: The high temperature resistant filler is one or more of white carbon black, silicon dioxide and calcium carbonate; White carbon black is white carbon black prepared by gas phase method or precipitation method, with an average particle size of 5 to 35 μm; The particle size of calcium carbonate is 4000 mesh and the moisture content is <0.1%.
5. The electric power insulation fireproof plugging glue according to claim 1 is characterized by: When drawing, the glass fiber, which is one of the warp and weft threads, passes through a space where ferroferric oxide powder dust floats in the air in a molten state, and is bonded with ferroferric oxide powder. As another type of warp and weft, glass fiber is passed through a space where graphite dust floats in the air in a molten state during drawing, and is bonded with graphite powder. The particle size of the ferroferric oxide powder is 50 to 150 nm; The particle size of graphite powder is 6 to 10 μm.
6. The electric power insulation fireproof plugging glue according to claim 1 is characterized in that: Also included is a mixture of gas storage particles detonated by magnetic force, with the gas storage particles as filler; The gas storage particles have an airtight membrane filled with air at 1.15 to 1.3 atmospheres and a humidity of 70 to 90%. Also included is a magnetic needle, which includes a needle tip and a needle body, the needle tip is made of a soft magnetic material, and the needle body is made of a non-magnetic material; The volume of gas storage particles is 2-3 mm 3 ; There are 2 to 4 gas storage particles per cubic centimeter.
7. The electric power insulation fireproof plugging glue according to claim 6 is characterized in that: The membrane of the gas storage particles is made of polyvinyl chloride; The needle tip is made of low carbon steel; the needle body is made of ABS plastic.
8. The electric power insulation fireproof plugging glue according to claim 1 is characterized in that: The preparation method of the power insulation fireproof plugging glue, the specific preparation steps are: S1. Activation treatment: Activate the high temperature resistant filler to improve its activity in subsequent reactions; S2. Base material mixing: Add the silicone base material and the fire retardant additive into the reactor according to the component ratio, close the reactor, start the vacuum device to draw vacuum in the reactor until the pressure in the reactor is lower than 130 Bar, and start the stirring device to stir to ensure uniform mixing; S3. Adding flame retardant: Add environmentally friendly flame retardant materials into the reactor, close the reactor and start the vacuum device to draw vacuum into the reactor until the pressure inside the reactor is lower than 130 Bar, start the stirring device and continue stirring until it is completely uniform; S4, dispersion treatment: add the activated high temperature resistant filler into the reactor, close the reactor again, and draw vacuum in the reactor again until the pressure in the reactor is lower than 130 Bar, and then perform dispersion treatment. The dispersion treatment time is 4 to 6 hours to ensure that the high temperature resistant filler is evenly dispersed in the silicone base material; S5. Testing and packaging: The prepared sealant is subjected to performance testing, and if qualified, it is packaged to obtain the finished product of power insulation fireproof sealing glue.
9. The electric power insulation fireproof plugging glue according to claim 8 is characterized by: The activation treatment in step S1 is carried out by using ultrasonic dispersion treatment, and the activation treatment lasts for 10 to 30 minutes; The stirring time of step S2 is 15 to 45 minutes; The stirring time of step S3 is 5 to 15 minutes; The dispersion treatment time of step S4 is 4 to 6 hours.